THE CRITICAL ANALYSIS OF DOGMATICS ON THE PRESUMPTION OF PATERNITY AND THE RIGHT TO IDENTITY - Isique-Morales, Marcos David (2020)
Objectives: Determine the perception of the doctrine on the regulatory framework that bases the presumption of paternity and the right to identity, on which the casuistry registered in a Judicial District of Lima will be evaluated. Materials and methods: A quantitative, descriptive and cross-sectional study was carried out. The population was made up of 63 respondents (among lawyers, prosecutors and judges) in the judicial district of Lima. The technique used was the survey and the collection instrument was prepared by the author and validated by expert judges. Results: In relation to the perception of the regulatory framework, most of them disagreed with 47.6% (n = 30), followed in agreement with 38% (n = 24), and the position of neutrality with 14% (n = 9). Regarding its dimensions: in the right to identity, where it is evaluated whether the current regulatory framework ensures the right to identity, the interviewees were neutral with 57.1% (n = 36), followed by disagreement with 38.1 % (n = 24), and the position according to 4.8% (n = 3) and regarding the legal security dimension, where it was evaluated if the current regulatory framework requires improvements to guarantee legal security, the interviewees mentioned being according to 49.2% (n = 31), followed by neutrality 33.3% (n = 21), and the position of disagreement with 17.5% (n = 11) Conclusions: Most of the interviewees are in disagreement with the regulatory framework that supports the presumption of paternity and the right to identity, because it does not guarantee legal security and violates identity